Implementation of Smoke Free Policy in the Workplace - Iriani, Atrika (FIA UB, 2018)
This paper aims to explain the implementation of smoke free policy in Palembang city. The research method uses qualitative research type sourced from human instrument, event and document. Data collection technique with indepth interview, observation, and documentation.Â The results of this study revealed that Implementation of smoke free policy in Palembang City has been implemented but there are still obstacles in the context of implementation such as lack of human resources, and implementation of local regulation KTR (no smoking area), lack of coordination between the Head of Institution and employees and the implementation of Justice Session to KTR offenders only limited to the provision of a reprimand, no one has been given administrative sanctions. So it is still found violations committed by tenants and visitors who smoke in the region without cigarettes. Factors that support the Implementation of local regulation KTR, including: has accommodated the Implementers of Policy Implementation, Head of Agencies and Public Interest. Availability of local regulation KTR stickers or the establishment of Internal Supervisory Team in Government Agencies in order to involve all security/Security Officers without exception.